PEMANFAATAN PROSEDUR STIMULASI BAGI GURU BAHASA INDONESIA - Syam, Christanto; Olendo, Yudhistira Oscar; Putra, Zakarias Aria Widyatama (Academy of Education Journal, 2023)
Stimulation procedures in Indonesian language learning need to be utilized by Indonesian language teachers, including at SMA N 9 Pontianak. This procedure is placed in apperception activities with the aim of being a solution for students to be more focused and have motivation for Indonesian language learning. The reason for utilizing stimulation procedures for teachers is because students have a lack of preparedness in receiving Indonesian language materials. Therefore, to dissect the flow of utilization of stimulation procedures for Indonesian language teachers, descriptive qualitative methods are used. Subjects and data sources are Indonesian language teachers with observation and interview data collection techniques. The data obtained is then analyzed by reducing data explanation, and conclusion. Based on review of the research scheme, it is revealed that Indonesian language teachers are ready to utilize stimulation procedures in the hope that Indonesian language learning can run effectively.